Roosting characteristics and feeding ecology of Indian flying fox (Pteropus medius Temminck, 1825): the importance of restricted urban green spaces in conservation (Bangladesh Journal of Zoology, 2026)
Present study investigated the roosting, diet and dietary composition, and conservation challenges of the Indian flying fox, Pteropus medius from April 2023 to March 2024. The study was based on monthly four to five days direct field observation walking through the trails laid over the study areas. The population was estimated by direct roost count methods (Kunz et al. 1996).  A total of 1940 individual of bats from 45 colonies were recorded. The bats were roosted in well-branched tall trees above or near water bodies in the city’s parks and gardens. Most roosts were permanent but varied insignificantly seasonally. Seventeen tree species of 11 families were used for roosting. The bats preferred well branched woody tall trees having a good crown to roost. Relationship between the bats abundance and diameter at breast height of the roosting trees (r = 0.647, n = 44, p < 0.000) and crown volume (r = 0.466, n = 44, p = 0.0011) were significant. Trees dbh explained 44% of the variation (R² = 0.449, n = 41, p = 0.001), while crown volume 22% (R² = 0.217, p = 0.05) in relation to the abundance of bats. Pteropus feeding observation included on site (n = 112) and out site (n = 68) bouts. They mostly fed on fruits (75.56%), followed by flowers (14.44%) and nectar (10%) respectively, while insect feeding observed occasionally. Feeding activities of the bats fluctuated significantly temporally (χ2 =22.11, df = 6, p = 0.0011). They fed on 15 plants species belonging to 11 families. Neolamarckia cadamba, Polylthia longifolia, Putranjiva roxburghii, Ficus benghalensis, Ficus glomerata, and F. racemosa were consumed round the year, even in the period of fall back. Habitat destruction, shrinkage and degradation of water bodies are the two major threats identified. The findings emphasize the importance of protecting the bats current roosting habitats and establishing enrichment plantation to improve their foraging areas and future long-term prospects for conservation of Pteropus medius in these areas.Bangladesh J. Zool. 53(3): 333-348, 2025